EXPERIENCE OF TREATMENT OF THE TWINS SICK WITH JUVENILE IDIOPATHIC ARTHRITIS BY ABATACEPT - V. A. Kel'tsev (Вопросы современной педиатрии, 2014)
The case of clinical observation over twin brothers (boys E. and N) suffering juvenile idiopathic arthritis is presented in the article. Boys fell ill with a difference in 1 year and 5 months at the age of 1 year and 9 months and 3 years 2 months, respectively. The disease proceeded wavily with the periods of remissions and exacerbations. Resistant articulate syndrome developed in July and November, 2009, respectively. Both children received NSAID, methotrexate combination in a dose of 10 mg/m2/week and sulphasalazine in a dose of 20 mg/kg of body weight per day. To the boy E. it was also prescripted prednisolon in a dose of 10 mg per day. Duration of antirheumatic therapy made 7 and 3 months, respectively. The therapy with a blocker of T-lymphocytes costimulation, abatacept, was initiated for the twins due to the inefficiency of treatment by immunodepressants and prednisolon at the boy E. In 6 weeks of the treatment 50% improvement, in 24 weeks — 90% improvement by criteria of the American College of Rheumatologists (ACRpedi) were registered. The undesirable phenomena weren’t observed.